The Oldest Hebrew Alphabetic Inscriptions (The Epigraphical Analysis) - Nowogórski, Przemysław (Saeculum Christianum. Pismo Historyczne, 2021)
Contemporarily the academia has six of the oldest Hebrew alphabetic inscriptions: ostracon from ʼIzbet Ṣartah (about 1200 BC), inscription from Tel Zayit (/ 11th / half of 10th century BC), ostracon from Chirbet Qeiyafa (decline 11th - the first half of 10th century BC – reign of Saul ); a new inscription from Chirbet Qeiyafa (dated as the previous one); new ostracon form Ophel, Jerusalem (11th or half of 10th BC – reign of Solomon, it is also the oldest Hebrew inscription from the area of Jerusalem); Gezer Calendar (second half of 10th BC – reign of Solomon or the first half of the ninth century BC). This article discusses the contemporary state of research on early Hebrew inscriptions. It also presents the author's own findings and related issues on ancient Hebrew epigraphic.